'Please tell me when you are in pain': A heartbreaking story of care, gried and female-canine companionship - Suvi Satama; Astrid Huopalainen (Wiley, 2022)
What could the underdeveloped research area of canine–human companionship teach us about gendered body work as well as offer to the field of organization studies more broadly? This paper responds to recent discussions on the animal in the organizational academy. We share an autoethnographic story of female–canine companionship as experienced by one of the authors of the paper and her beloved dog, who is currently living on the borderlines between life and death, joy and mourning. We find this example relevant for raising important feminist concerns among organizational scholars about silenced questions around care and grief as well as for developing more inclusive and ethically grounded approaches to exploring research topics dealing with vulnerability. Finally, this paper offers a critical reflection on the potential and limitations of alternative research in the field of organization studies that recognizes our affective relations with animals.